THE INNOVATIVE MANAGEMENT PRINCIPLES OF RURAL SOCIAL INFRASTRUCTURE DEVELOPMENT - Atkociuniene, Vilma; Kiausiene, Ilona; Urmoniene, Daiva (European Scientific Journal, ESJ, 2014)
This article describes management of rural social infrastructure (hereinafter referred to as the RSI), provides the analysis of RSI management processes and determination of main principles required in order to achieve efficient management of rural areas and sustained development of the region. The main research objective, namely, creation of a modern rural social infrastructure management approach has been reached. The main elements of the modern RSI management conception were identified: determination of consumer demand for RSI services and strategic development goals; RSI development (planning of services, means and results); organization of RSI services supply; horizontal and vertical coordination of RSI activities; assessment of RSI services consumers’ opinion and community sustainability; supervision and evaluation of RSI activities. The main principles for RSI management were defined: coordination of principles “from top to bottom” and “from bottom to top”; satisfaction of social needs and local initiatives; partnership and division of responsibility; involvement of local residents and decentralization of decision making processes; continuous study, professional development and stimulation of self-esteem; Integrity and hierarchy; innovations, readiness for changes, efficiency; ecology. The main research methods were used: analysis and generalization of scientific literature, logical and systematical reasoning, graphic presentation of comparison, abstracts and other methods.